ANALISIS FAKTOR-FAKTOR RENDAHNYA MINAT BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV DI SD 190 PALEMBANG - Waiz Alkarni; Susanti Faipri Selegi; David Budi Irawan (PT. Jurnal Center Indonesia Publisher, 2025)
This research is descriptive research and uses qualitative methods. This research aims to analyze the factors of students' low interest in learning in grade IV science and science subjects at SD 190 Palembang, totaling 16 students. The sampling technique in this research uses the proportional sampling method, In this study, the data taken was in the form of interview data, questionnaires and documentation in carrying out this research. The first step taken by the researcher was distributing questionnaires to students. The questionnaire was closed with 5 answer choices, namely strongly agree, agree, neutral, disagree and strongly disagree. agree, the questionnaire instrument consists of 21 statement items. Next, carry out the interview stage which is carried out after giving a questionnaire consisting of 10 questions and then carry out the documentation stage which shows that there are several students whose scores are below the Kkm, namely 75. So the indicator that can be concluded is the feeling of happiness indicator which is 12.79%, while The indicator of student interest was 13.21%, then the indicator of student attention was 14.5%, then the indicator of student involvement was 20.95%. In terms of indicators of student interest in science and science subjects, the percentage results were 13.21% with poor criteria.